High-calorie diets uncouple hypothalamic oxytocin neurons from a gut-to-brain satiation pathway via κ-opioid signaling - Gruber, Tim; Lechner, Franziska; Murat, Cahuê; Contreras, Raian E.; Sanchez-Quant, Eva; Miok, Viktorian; Makris, Konstantinos; Le Thuc, Ophélia; González-García, Ismael; García-Clave, Elena; Althammer, Ferdinand; Krabichler, Quirin; et al. (Cell reports, 2023)
Oxytocin-expressing paraventricular hypothalamic neurons (PVNOT neurons) integrate afferent signals from the gut, including cholecystokinin (CCK), to adjust whole-body energy homeostasis. However, the molecular underpinnings by which PVNOT neurons orchestrate gut-to-brain feeding control remain unclear. Here, we show that mice undergoing selective ablation of PVNOT neurons fail to reduce food intake in response to CCK and develop hyperphagic obesity on a chow diet. Notably, exposing wild-type mice to a high-fat/high-sugar (HFHS) diet recapitulates this insensitivity toward CCK, which is linked to diet-induced transcriptional and electrophysiological aberrations specifically in PVNOT neurons. Restoring OT pathways in diet-induced obese (DIO) mice via chemogenetics or polypharmacology sufficiently re-establishes CCK’s anorexigenic effects. Last, by single-cell profiling, we identify a specialized PVNOT neuronal subpopulation with increased κ-opioid signaling under an HFHS diet, which restrains their CCK-evoked activation. In sum, we document a (patho)mechanism by which PVNOT signaling uncouples a gut-brain satiation pathway under obesogenic conditions.
Online verfügbar 31 October 2023, Version des Artikels 31 October 2023
Gesehen am 29.01.2024